User Behavior Analysis on a Simulated Academic Information Website Using the Microsoft Clarity Heatmap Method - Nisa Ayu Cahyaningrum; Taufiq Agung Cahyono; Joko Iskandar (Universitas Mohammad Husni Thamrin, 2026)
The advent of digital technology over the past decade has transformed the way higher education institutions deliver services to their academic communities. Digital transformation has positioned academic websites as the primary communication channel between students and higher education institutions, yet interface evaluation continues to rely on perception-based methods that fail to capture actual user behavior. This study analyzes interaction patterns of users on a simulative academic information website, identifies interface elements that create friction, and proposes evidence-based design improvements. A quantitative descriptive approach was adopted using Microsoft Clarity as the data collection instrument, which automatically recorded click heatmap, scroll heatmap, movement heatmap, and session replay data. Thirty interaction sessions from 21 unique users were gathered through purposive sampling of active students at Bhinneka PGRI University Tulungagung. The findings reveal that click intensity was concentrated on the homepage and the